Guidelines for Curriculum for Library and Information Science Education and Training in India in the Nineties - Rajan, T. N.; Satyanarayana, R. (Journal of Information and Knowledge, 2014)
States a few premises on which the paper is based. Identifies a few parameters for professional preparation. Mentions a few ideas in drafting a course modules which should include a learning and teaching package. Outlines course contents for library and Information Science courses at bachelors and masters levels.